2004
DOI: 10.1002/chem.200304810
|View full text |Cite
|
Sign up to set email alerts
|

High Oxidation State Organometallic Chemistry in Aqueous Media: New Opportunities for Catalysis and Electrocatalysis

Abstract: Molybdenum has been used as a case study for the rational development of a new domain of organometallic chemistry, combining oxo-stabilized high oxidation state metals and aqueous media. The pH-dependent conversion of oxo, hydroxo, and aqua ligands allows the opening of free coordination sites, while the use of a redox active metal opens possible pathways for coupled proton and electron transfer to and from activated substrates. While our work has so far only concentrated on synthesis and analytical investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…For this reason, we thought that a new theoretical investigation of the epoxidation mechanism was warranted. [44] We are interested in the aqueous chemistry of the Cp*Mo VI system [45] and have shown that compound [Cp* 2 Mo 2 O 5 ] self-ionizes in water to yield a 1:…”
Section: Cp*moo(oh)a C H T U N G T R E N N U N G (Oor)cl] or [Cp*moo(mentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, we thought that a new theoretical investigation of the epoxidation mechanism was warranted. [44] We are interested in the aqueous chemistry of the Cp*Mo VI system [45] and have shown that compound [Cp* 2 Mo 2 O 5 ] self-ionizes in water to yield a 1:…”
Section: Cp*moo(oh)a C H T U N G T R E N N U N G (Oor)cl] or [Cp*moo(mentioning
confidence: 99%
“…[47] Therefore, we decided to examine the mechanism of the olefin epoxidation process by both Bergmans [Cp*MoO 2 It should also be noted that in a recent contribution, Colbran et al have shown that a (perarylcyclopentadienyl)molybdenum(VI) dioxido complex, although catalytically active in cyclooctene epoxidation by TBHP, decomposes to a more active non-cyclopentadienyl-containing catalyst as the reaction proceeds. [48] However, an equivalent protonolysis is not necessarily associated also with the more robust [45] Cp* À Mo bond. Furthermore, the isolobal relationship indicated in Scheme 5 makes a mechanistic investigation carried out for the Cp*Mo species also relevant to a putative product of hydrolytic decomposition.…”
Section: Cp*moo(oh)a C H T U N G T R E N N U N G (Oor)cl] or [Cp*moo(mentioning
confidence: 99%
“…Other recent relevant reviews have appeared on organometallic oxides [34] and hydroxides [35] of the transition elements, as well as on dioxygen activation by organometallics of the early transition metals [36]. A concept article and a special report highlighting advances from our own group in aqueous Cp * Mo chemistry have also been published a few years ago [37,38]. Finally, a recent review by Kühn et al highlights the synthesis, reactivity and catalytic applications of mononuclear organomolybdenum(VI) dioxido complexes [39].…”
Section: Introductionmentioning
confidence: 99%
“…[6] Although this area is widely explored for low-valent systems, usually upon appending hydrophilic functionalities to the ligand periphery to increase solubility in an aqueous environment, [7][8][9] studies of high-oxidation organometallics are still rather scarce. [10][11][12] For redox-active metals, these studies are particularly interesting, as they may open the way to electrocatalytic applications. [12] In a recent contribution, [13] we reported that the zinc reduction of Cp* 2 Mo 2 O 5 in a strongly acidic (CF 3 atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] For redox-active metals, these studies are particularly interesting, as they may open the way to electrocatalytic applications. [12] In a recent contribution, [13] we reported that the zinc reduction of Cp* 2 Mo 2 O 5 in a strongly acidic (CF 3 atoms. The two-electron cluster is diamagnetic.…”
Section: Introductionmentioning
confidence: 99%